2012
DOI: 10.1523/jneurosci.4497-11.2012
|View full text |Cite
|
Sign up to set email alerts
|

Event-Related Nociceptive Arousal Enhances Memory Consolidation for Neutral Scenes

Abstract: The superior memory for emotional events has been attributed to the beneficial effects of noradrenaline released into the amygdala attributable to arousal. Noradrenaline mediates the effects of different hormones and neurotransmitters, including adrenal stress hormones on consolidation ( Recently, it was highlighted that emotional stimuli elicit not only arousal but also intensify cognitive processes that contribute to the enhanced memory. In particular, the enhanced use of selective attention as well as the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
53
4
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 59 publications
6
53
4
1
Order By: Relevance
“…Positive stimuli, whether delivered under a constant or intermittent schedule during learning, had no effect on parahippocampal activation relative to neutral stimuli, although arousal levels were matched independently for positive and negative stimuli. Similar to previous studies that have shown memory enhancement for negative emotional stimuli (Schwarze et al, 2012;Keightley, Chiew, Anderson, & Grady, 2011;Humphreys, Underwood, & Chapman, 2010;Mickley Steinmetz, Addis, & Kensinger, 2010;Mickley & Kensinger, 2008), our finding suggests that affectively modulated place memory is valence-specific. Our findings are also consistent with previous studies that have shown that the parahippocampal gyrus is specifically involved in the processing of negative emotional stimuli but not positive emotional stimuli (Aldhafeeri, Mackenzie, Kay, Alghamdi, & Sluming, 2012;Gosselin et al, 2006).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Positive stimuli, whether delivered under a constant or intermittent schedule during learning, had no effect on parahippocampal activation relative to neutral stimuli, although arousal levels were matched independently for positive and negative stimuli. Similar to previous studies that have shown memory enhancement for negative emotional stimuli (Schwarze et al, 2012;Keightley, Chiew, Anderson, & Grady, 2011;Humphreys, Underwood, & Chapman, 2010;Mickley Steinmetz, Addis, & Kensinger, 2010;Mickley & Kensinger, 2008), our finding suggests that affectively modulated place memory is valence-specific. Our findings are also consistent with previous studies that have shown that the parahippocampal gyrus is specifically involved in the processing of negative emotional stimuli but not positive emotional stimuli (Aldhafeeri, Mackenzie, Kay, Alghamdi, & Sluming, 2012;Gosselin et al, 2006).…”
Section: Discussionsupporting
confidence: 91%
“…It is perhaps not surprising therefore that we did not find significant amygdala activity for any of the place stimuli during scanning. A recent fMRI study that examined the influence of nociceptive stimuli on memory for neutral pictures also found no significant increase in amygdala activity during retrieval, despite evidence for enhanced activity in a number of other brain regions, including the parahippocampal gyrus (Schwarze et al, 2012). The affective salience of learned locations, although mediated via the amygdala during encoding and consolidation, is likely to be stored independently within the parahippocampal gyrus for later retrieval (Cahill & McGaugh, 1998;Packard, Cahill, & McGaugh, 1994).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Imaging studies have also provided evidence, consistent with evidence obtained with animal studies, that emotional arousal influences on consolidation of long-term memory involve interactions of the amygdala with other brain regions, including the hippocampus, during learning (126)(127)(128)(129)(130)(131)(132). Findings of human brain imaging studies using functional MRI provide additional evidence that emotional arousal influences on memory involve noradrenergic activation of the amygdala.…”
Section: Amygdala Influences On Other Brain Systemssupporting
confidence: 72%
“…Because blood pressure and heart rate were back to normal levels only 3 hr after propranolol administration (i.e., 1-1.5 hr after encoding), a decrease in physiological arousal during initial memory consolidation could have counteracted arousal-mediated memory consolidation processes resulting in lower subjective recollection in the group that received propranolol at encoding. On the contrary, prior studies have shown that postlearning arousal selectively enhances familiarity, rather than recollection of neutral information presented beforehand (McCullough & Yonelinas, 2013;Schwarze, Bingel, & Sommer, 2012;Yonelinas, Parks, Koen, Jorgenson, & Mendoza, 2011). Thus, future studies are needed to determine the role of physiological arousal during encoding versus consolidation and its relation to the subjective recollective experience.…”
Section: Discussionmentioning
confidence: 93%